Alcohol, alcoholism and related consequences - M. V. Mayevskaya (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To analyze problem of alcohol abuse and dangerous consequences related to it in Russian population, to demonstrate possible ways of its decision.The basic contents. According to official statistics, alcohol is one of leading factors of mortality in Russian population, making 11,9%. Almost in half of deceased population (47,7%) lethal outcome was caused by fatal changes of internal organs, in one fifth (21,7%) – by accidents. Moreover, 35% of patients with alcoholism die in the age most effective for various forms of activity (i.e. 20–50 years). Combined efforts of government institutions, medical community, professional organizations are necessary for resolution of this issue. Position of the State is very clear – to reduce the harm of alcohol to the population by the year 2020. Medical community, viz. internist doctors, should be ready to take active part in the decision of alcohol dependence problem, and not just to pay attention to somatic issues related to their specialty. The proper motivation of the patient by doctor is extremely actual for those, who take alcohol in dozes dangerous for health, as well as for those who drinks too much and too fast. For these purposes there are specially developed techniques – motivational interviews, in particular technique of brief interventions. Special techniques are applied in motivational interview: empathy (realized compassion to current emotional status of the other person), reflective listening (conducting thematically directed dialogue between psychologist and the patient to obtain data), resistance following, account of actual readiness for changes and actual needs, achievement of specific targets with assessment of specific effects. Pharmaceutical therapy of alcohol-induced dependency made a major step forward as well with introduction of new class of drugs – opioid system modulators represented by nalmefene and naltrexone. Opioid receptors are involved in development of alcohol-induced dependency. Nalmefene, blocking these receptors, reduces supporting effect of alcohol which ceases to deliver expected pleasure.Conclusion. Successful campaign against alcoholism is possible only at application of all resources: strategy of the state, involvement of internist doctors in problem decision (application of motivational conversation technic), pharmaceutical therapy directed on reduction of amount alcoholic drinks.